2003
DOI: 10.1023/a:1026156130656
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis participates to liver damage in HSV-induced fulminant hepatitis

Abstract: These data as a whole show that apoptosis is responsible, at least partially, for liver damage during HSV fulminant hepatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 40 publications
1
10
0
1
Order By: Relevance
“…HSV-1 Cgal ϩ results from the reinsertion of both ICP4 copies in Cgal⌬3 backbone, and therefore it might be able to block host cell apoptosis upon infection. The observed proapoptotic behavior of HSV-1 Cgal ϩ in human liver cancer Huh7 cells might be explained assuming that liver cells are specially sensitive to HSV-induced apoptosis, as previously proposed (43)(44)(45). In addition, proapoptotic HSV-1 variants lacking viral antiapoptotic proteins induce programmed cell death preferentially in human cancer cells (7).…”
Section: Fig 5 Cgalsupporting
confidence: 51%
“…HSV-1 Cgal ϩ results from the reinsertion of both ICP4 copies in Cgal⌬3 backbone, and therefore it might be able to block host cell apoptosis upon infection. The observed proapoptotic behavior of HSV-1 Cgal ϩ in human liver cancer Huh7 cells might be explained assuming that liver cells are specially sensitive to HSV-induced apoptosis, as previously proposed (43)(44)(45). In addition, proapoptotic HSV-1 variants lacking viral antiapoptotic proteins induce programmed cell death preferentially in human cancer cells (7).…”
Section: Fig 5 Cgalsupporting
confidence: 51%
“…Consistent with this finding, ALT did not increase in the plasma. In human acute and fulminant hepatitis, apoptotic changes of hepatocyte are frequent, but massive necrosis and elevation of transaminase also occur [20,41,48] different from the present model. It is reported that hepatocyte apoptosis induces transmigration of neutrophils which mediate hepatocyte necrosis [19].…”
Section: Discussionmentioning
confidence: 71%
“…In the context of liver disease, overactivation of the apoptotic process may lead to hepatocellular damage, while the inhibition of apoptosis may promote cell proliferation and transformation. Fulminant hepatic failure, induced by drugs, toxins or viral hepatitis, is characterized by severe hepatocellular dysfunction with a massive death of hepatocytes, in which apoptosis may play a role in addition to necrosis (4). d -galactosamine ( d -GalN) is a specific hepatotoxic agent metabolized exclusively in hepatocytes, which reduces the intracellular pool of uracil nucleotides, thus inhibiting the synthesis of RNA and proteins (5).…”
Section: Introductionmentioning
confidence: 99%